Reproductive Biology of Yellow-Finned Barb (Mystacoleucus marginatus, Valenciennes 1842) in the Lau Belawan River, North Sumatra Province - Desrita, Desrita (Indonesian Fisheries Research Journal, 2025)
Lau Belawan River has a fish potential, including yellow-finned barb (Mystacoleucus marginatus. The objective of this study was to investigate the reproductive biology of the yellow-finned barb (Mystacoleucus marginatus, Valenciennes 1842) in the Lau Belawan River, North Sumatra Province. The research location consists of 3 stations. Fish samples were collected by capturing fish using a low-voltage backpack electrofishing unit.  Determination of the sex ratio is done surgically, then the results are tested using chi-square statistics, gonad maturity index obtained by comparing body weight with gonad weight, and estimation of the size of the first mature gonad using the Sperman-Karber method. The fish caught during the study amounted to 165 fish collected from 3 research stations: Namorih Village, where station 1 collected 146 fish; Kampung Tengah Village station 2, with a total catch of 148 fish; and Baru Ladang Bambu Village station 3, with samples collected of 222 fish. The Lau Belawan River habitat supports the existence of aquatic biota such as fish and plankton. The sex ratio of yellow-finned barb fish is balanced in November and December except in October, January, February, and March. Female fish mature gonads dominantly in November, December, and March, while males mature in October, January, and March. Spawning occurred every month, with peak spawning occurring in March. Male and female gonad mature yellow-finned barb fish are present at each station, indicating that the research station is a suitable habitat for spawning fish.